Reduction of return temperatures in urban district heating systems by the implementation of energy-cascades. (June 2017) - Köfinger, Markus; Basciotti, Daniele; Schmidt, Ralf-Roman
Abstract: High return temperatures in district heating networks are a significant barrier for the transformation into 4th generation systems. In order to transport high amount of heat in winter times, there is the need of increased supply temperatures (>120 °C) or mass flow rates due to high return temperatures. This leads to an inefficient operation of the system. High heat losses, decreased efficiency of heat production units, reduced potential of alternative heat sources and increased pumping costs are the consequences. Further is the connection of new customers often linked with high investment costs due to limited transport capacities in an existing system. The aim of this paper is to analyse potentials and to develop concepts to reduce return temperatures by implementing thermal energy cascades between different building types in order to improve the performance of the system. This is related to the use of the return flow of high-temperature consumers (e.g. buildings with high-temperature heating systems) for supplying low-temperature consumers (e.g. buildings with floor heating and direct domestic hot water preparation). Based on available data from existing buildings, energy suppliers and network structures, potentials for energy-cascades for representative case studies have been evaluated. To enable energy cascaded interconnections, the temperature and heat load profiles of the investigated buildings in characteristic districts were analysed and different connection scenarios were developed and evaluated. Special attention was given to the hygienic preparation of domestic hot water in the low-temperature consumers and the security of the heat supply. As a result, the temperature level of the local return line could be reduced (up to >10 K) and transport capacities in the districts were increased (up to 16 %). By implementing this approach in several districts of an urban network, the overall system efficiency can be increased.